Assessing a Human Rights-Based Approach to HIV in Kenya - Neiloy R. Sircar; Tabitha G. Saoyo; Allan A. Maleche (Harvard FXB Center for Health and Human Rights, 2019)
Kenya is actively encouraging HIV testing and notification services in order to identify persons living with HIV and link them to treatment. Recently, Kenya and international supporters of its HIV program have sought to scale up these services through increased capacity and training. However, little is known about how this strategy has been implemented and is being sustained, particularly regarding the human rights of persons living with or at risk for HIV. This exploratory qualitative study seeks perspectives from health providers and populations at risk for HIV, including young women, men who have sex with men, sex workers, and injection drug users. Our primary data collection methods will be focus group discussions and in-depth interviews. We will transcribe and analyze data under a grounded theory approach to compare outputs from populations at risk for HIV with outputs from health providers. We will also apply a rights analysis to the data's codes and themes to assess how effectively Kenya's HIV strategy, policies, and practices adhere to a human rights-based approach. The results will support both rights realization among at-risk populations and the public health objectives for HIV testing and treatment.